Surface modification by physical treatments on biomedical grade metals to improve adhesion for bonding hybrid non-isocyanate urethanes - Rossi de Aguiar, K. M. F.; Specht, U.; Maass, J. F.; Salz, D.; Picon, C. A. [UNESP]; Noeske, P. -L. M.; Rischka, K.; Rodrigues-Filho, U. P. (Royal Soc Chemistry, 2016)
This work aims to improve the adhesion of a hybrid non-isocyanate polydimethylsiloxane urethane (PDMSUr) coating by producing active layers on titanium alloy (Ti6Al4V) and stainless steel (SS316L) applying pulsed Nd:YAG laser and oxygen plasma. The PDMSUr is a hybrid adhesive and, when functionalized with alkoxysilane groups, can bind onto the interfacial hydroxyl groups of a (hydr)oxide/carbonate layer by sol-gel reactions. These reactions are acid catalysed and the silanol groups can bind through Si-O-metal links. The pull-off-strength of such sustainable coatings raised more than 100% for both substrates after the physical treatments, compared with the substrates etched. X-ray Photoelectron Spectroscopy (XPS) of a freshly pre-treated substrate revealed the formation of thin oxide-based reactive layers on the surface of Ti6Al4V and SS316L after the surface treatments. Both physical procedures were efficient to create oxide layers on top of metallic substrates and contributed to the improvement of adhesion strength of PDMSUr on biomedical grade metals.